Enantioselective Organocatalyzed Domino Synthesis of Six-Membered Carbocycles - Goudedranche, Sébastien; Raimondi, Wilfried; Bugaut, Xavier; Constantieux, Thierry; Bonne, Damien; Rodriguez, Jean (Synthesis, 2013)
Polysubstituted chiral cyclohexanes and cyclohexenes are important building blocks in organic synthesis. From historical and pioneering reports to the most recent accounts, this review focuses on domino enantioselective organocatalytic methodologies that have allowed the control of the relative and absolute configurations of up to six stereogenic centers in the construction of these versatile molecular architectures.1 Introduction2 Two-Component Transformations2.1 Michael-Initiated Domino Reactions with α,β-Unsaturated Carbonyl Compounds2.2 Michael-Initiated Domino Reactions with Nitroolefins2.3 Non Michael-Initiated Domino Reactions3 Multicomponent and Related Transformations3.1 Pseudo-Three-Component Reactions3.1.1 Michael-Initiated Domino Reactions with Nitroolefins3.1.2 Michael-Initiated Domino Reactions with α,β-Unsaturated Carbonyl Compounds3.2 Consecutive Reactions3.2.1 Michael-Initiated Domino Reactions with Nitroolefins3.2.2 Michael-Initiated Domino Reactions with α,β-Unsaturated Carbonyl Compounds3.3 Multicomponent Reactions3.3.1 Michael-Initiated Domino Reactions with Nitroolefins3.3.2 Michael-Initiated Domino Reactions with α,β-Unsaturated Carbonyl Compounds4 Conclusion
Keywords: organocatalysis; domino reactions; multicomponent reactions; cyclohexanes; cyclohexenes; asymmetric synthesis